Use of amlodipine to treat postpartum hypertension - Hannah Gerretsen; Melanie Nana; Catherine Nelson-Piercy (Obstetric Medicine, 2026)
Background Hypertension can arise de novo or persist in the postnatal period. Limited data exist regarding the use of amlodipine in the postpartum period. Materials and methods A service evaluation of women prescribed amlodipine postnatally in the maternity department at Guy's and St Thomas’ NHS Foundation Trust from April to November 2020 was conducted. Data were obtained by reviewing hospital records and conducting a telephone survey. Results Of the 100 women who were prescribed postnatal amlodipine, 43 completed the telephone survey and were included in the analysis. There were no stillbirths, neonatal deaths or significant congenital malformations. Duration of treatment varied from less than 1 week to 1 year postpartum. None of the women taking amlodipine during breastfeeding reported any problems: 23/43 (53.5%) exclusively breastfed and 10/43 (23.3%) mixed-fed. Discussion We report the largest case series of postpartum amlodipine use, providing reassuring data regarding its safety and efficacy in this population.